Comparative evaluation of air-Q and classic laryngeal mask airway for surgeries under anesthesia: A randomized open-label trial - Susheela Taxak; Pooja Jaju Bihani; Rishabh Jaju; Kirti Kamal; Mangal Ahlawat; Priyanka Sethi; Raksha Vyas (The Indian Anaesthetists' Forum, 2019)
Objective: Classic laryngeal mask airway (cLMA) is a prototype supraglottic airway device, and Air-Q is a newly introduced device for use as a primary airway and as an aid for intubation. Due to paucity of literature comparing Air-Q with cLMA, this prospective, randomized, single-blinded study was performed, to evaluate their clinical performance as a primary airway conduit. Methods: Sixty patients of either sex with the American society of anesthesiology Grade I or II, weighing between 50 and 70 kg, were randomly allocated to either the cLMA (n = 30) or Air-Q (n = 30) group. After induction of anesthesia, the assigned airway device was introduced. The ease of insertion, vital parameters, oropharyngeal seal pressure (OSP), airway morbidity, and fiberoptic grades of laryngeal view was recorded. Results: There was no significant difference in ease of insertion, the time taken for successful device placement, number of attempts, or postoperative morbidities. Air-Q was found better with respect to hemodynamic stability during placement of the device. There was a significant difference in the OSP between the Air-Q (22.12 ± 1.740 cm H2O) and cLMA (16.28 ± 2.052 cm H2O), P < 0.001. Fiberoptic laryngeal view through Air-Q was also superior (P < 0.001). Conclusion: Air-Q was found to be superior to cLMA for controlled ventilation in view of better OSP and a superior fiberoptic laryngeal view.